PENGARUH SELF-EFFICACY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI STATISTIKA KELAS VIII - Haqqul, Arinal; Saraswati, Sari (Cartesian: Jurnal Pendidikan Matematika, 2023)
Self-efficacy is an individual's belief in their ability to manage and organize the steps needed to achieve their goals. Students' confidence in the subject being studied is very important in solving problems. The purpose of this study was to determine the effect of self-efficacy on mathematical problem solving abilities in class VIII statistics material. The method used in this research is a survey. The research subjects were students of class VIII which consisted of 38 students. Test and questionnaire methods were used for data collection techniques. Data analysis technique with the help of SPSS 25 software with normality test, linearity test, and simple linear regression test. The results of the study stated that self-efficacy had no effect on the ability to solve mathematical problems in statistical material for class VIII A SMP Islam Mbah Bolong with regression equations .